Pengaruh Metode Practice Rehearsal Pairs (Praktik Berpasangan) Terhadap Motivasi Belajar Siswa Pada Pembelajaran Tematik Kelas IV SD Negeri 001 Rambah - Rejeki Rejeki (JURNAL PENDIDIKAN ROKANIA, 2022)
This research was conducted at SD Negeri 001 Rambah in the 2021/2022 academic year. The research model is Quasy Experiment and the researcher chose a Quasi Experiment Design research design with the type of pretest-posttest. The population in this study was all fourth grade students at SD Negeri 001 Rambah in the 2021/2022 academic year which consisted of 44 people who were divided into 2 classes. Taking the experimental class and control class using the Random Sampling technique (random class). The sample in this study amounted to 44 students. Class VI B as the experimental class used the Practice Rehearsal Pair method and class VA as the control class used the conventional method. The data collection technique method used is the questionnaire method. Based on the calculation of the hypothesis test that has been carried out in the experimental class and control class, it is obtained that TCount is 0,012798646 T-table is 0,4227 so T-Count < TTable, which means H1 is accepted and H0 is rejected. So it can be concluded that there is significant effect between the Practice Rehearsal Pair methods on students' learning motivation in the thematic learning of Class IV SD Negeri 001 Rambah.